James, First Peter, Jude, Second Peter - Hartin, P. J. (Patrick J.) (Collegeville, Minn. : Liturgical Press, 2006)
"Complete biblical texts with sound, scholarly based commentary that is written at a pastoral level; the Scripture translation is that of the New American Bible with Revised New Testament and Revised Psalms (1991)"--Provided by publisher.
The general letters -- The letter of James : introduction, text, and commentary -- The first letter of Peter : introduction, text, and commentary -- The letter of Jude, introduction, text, and commentary -- The second letter of Peter : introduction, text, and commentary.
Includes index.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries; Bible. -- Commentaries